2021
DOI: 10.1016/j.heliyon.2021.e07628
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to students' satisfaction with holding e-learning during the Covid-19 pandemic based on the dimensions of e-learning

Abstract: Factors related to students' satisfaction with holding e-learning during the Covid-19 pandemic based on the dimensions of e-learning, HELIYON, https://doi.org/10.1016/j.heliyon.2021.e07628. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 25 publications
3
64
1
4
Order By: Relevance
“…The present study showed that satisfaction with e-learning increased with age. This finding was supported by some research [55], but contradicted by others [56] that found no significant relationship between student age and e-learning satisfaction. There may be various reasons for our findings, and the disparity between our findings and those of earlier research could be related to changes in the sample size, target demographics, or study scheduling [56].…”
Section: Discussionmentioning
confidence: 53%
“…The present study showed that satisfaction with e-learning increased with age. This finding was supported by some research [55], but contradicted by others [56] that found no significant relationship between student age and e-learning satisfaction. There may be various reasons for our findings, and the disparity between our findings and those of earlier research could be related to changes in the sample size, target demographics, or study scheduling [56].…”
Section: Discussionmentioning
confidence: 53%
“…The outer side of the user has not been observed in the success of e-learning. According to (Yekefallah et al, 2021); (Hassanzadeh et al, 2012); (Ouajdouni et al, 2021), the successful adoption of e-learning can be caused by the quality of the system, characteristics of the instructor, e-learning environment, service quality, and instructional design made by the Faculty. So for future research, it is better to explore the external influence of individuals that affect the success of e-learning.…”
Section: Discussionmentioning
confidence: 99%
“…Around the education system, these measures have led to reconsider the place given to e-Learning, compared to traditional learning ( Maqableh and Alia, 2021 ). Teachers and tutors are now forced to rethink their teaching methods as well as the learning tools used and to appeal to online learning to resolve the problem linked to the conjunction of physical distancing and educational continuity during the period of sanitary confinement ( Yekefallah et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%